High-Breakdown and Low-Leakage 4H-SiC MOS Capacitor Based on HfO2/SiO2 Stacked Gate Dielectric in Trench Structures - Qimin Huang; Yunduo Guo; Anfeng Wang; Lin Gu; Zhenyu Wang; Chengxi Ding; Yi Shen; Hongping Ma; Qingchun Zhang (Nanomaterials)
The progression of SiC MOSFET technology from planar to trench structures requires optimized gate oxide layers within the trench to enhance device performance. In this study, we investigated the interface characteristics of HfO2 and SiO2/HfO2 gate dielectrics grown by atomic layer deposition (ALD) on SiC trench structures. The trench structure morphology was revealed using scanning electron microscopy (SEM). Atomic force microscopy (AFM) measurements showed that the roughness of both films was below 1nm. Spectroscopic ellipsometry (SE) indicated that the physical thicknesses of HfO2 and SiO2/HfO2 were 38.275 nm and 40.51 nm, respectively, demonstrating their comparable thicknesses. X-ray photoelectron spectroscopy (XPS) analysis of the gate dielectrics revealed almost identical Hf 4f core levels for both HfO2 and the SiO2/HfO2 composite dielectrics, suggesting that the SiO2 interlayer and the SiC substrate had minimal impact on the electronic structure of the HfO2 film. The breakdown electric field of the HfO2 film was recorded as 4.1 MV/cm, with a leakage current at breakdown of 1.1 × 10−3A/cm2. The SiO2/HfO2 stacked film exhibited significantly better performance, with a breakdown electric field of 6.5 MV/cm and a marked reduction in leakage current to 3.7 × 10−4 A/cm2. A detailed extraction and analysis of the leakage current mechanisms were proposed, and the data suggested that the introduction of thin SiO2 interfacial layers effectively mitigated small bandgap offset issues, significantly reducing leakage current and improving device performance.